Effect of Project-Based Learning Strategy on Students’ Interest and Performance in Science in Calabar Municipality, Cross River State - Anari, Mary Ideba; Neji, Hope Amba; Agube, Chukwu Chukwu (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
This study investigated the impact of project-based learning on students’ interest and academic performance in science in Calabar municipality local government area of Cross River state. The study adopted a pre-test, posttest quasi-experimental research design. Two research questions and hypotheses guided the study. The sample comprised 150 SSII students drawn from a population of 2100 students in the study area. The research instrument was a researcher-made test, tagged Science Achievement Test(SAT), with a reliability estimate of 0.80 using Kuder-Richardson, R-20, and a student interest questionnaire with a reliability index of 0.70 using Cronbach's alpha reliability estimate. The da a collected were analysed using descriptive and ANCOVA statistical tools. The result revealed that there was statistically significant difference in the student’s academic achievement F(1, 146) = 29.85, p < 0.000.with a mean gain score of 52.35 and the level of interest of students on the concept taught F(1, 147) = 2.75, p < 0.000 in favour of those in PBL group with with a mean gain of 23.25. It is recommended that science teachers integrate project-based learning in the science classroom to enhance students' understanding of science concepts and stimulate interest in science.